VILLAGE GOVERNMENT POLICIES IN MANAGING CASE OF EARLY MARRIAGE IN PANDEMIC TIMES - Siti Atika Rahmi; Rohana Rohana; Selva Selva (Wacana Hukum, 2021)
During the COVID-19 pandemic, cases of early marriage continued to increase. Therefore this research was conducted to find out how the policies that will be carried out by the Lepak village government in tackling the case of early marriage. The data sources used in this research are primary data in the form of interviews, field observations and documentation. From the results of interviews and observations made, is shows that the policies that have been carried out by the Lepak Village government in dealing with cases of early marriage during the pandemic covid-19 are in the form of routine socialization and counseling about the impacts that will occur have been agreed upon by the family and village officials.